Whistler‐Mode Transmission Experiments in the Radiation Belts: DSX TNT Circuit Simulation and Data Analysis. Issue 4 (11th April 2023) - Tu, Jiannan; Song, Paul; Galkin, Ivan A.; Reinisch, Bodo W.; Johnston, William R.; Starks, Michael J.; Su, Yi‐Jiun; Cooke, David; Ginet, Gregory P.; Inan, Umran S.; Lauben, David S.; Miyoshi, Yoshizumi; et al.
Abstract: High‐power transmission experiments in the very low frequency (VLF) mode have been conducted by the US Air Force Research Laboratory's Demonstration and Science Experiments (DSX) satellite in the radiation belts using a novel transmitter that automatically tunes to find the resonance frequency of the transmitter circuit including the antenna. The resulting voltage–frequency curves are used to derive antenna impedance at the resonance. The analysis shows that the antenna reactance is far less than that of a dipole antenna in free space. The derived radiation resistance is up to several tens of kilo Ohms. Most interestingly, it is found that the radiation resistance is inversely proportional to the square of transmission wave frequency. The transmitted power can be up to 80 W for the DSX transmitter with an 82‐m long tip‐to‐tip antenna, showing that the high‐power VLF transmission is feasible. Whistler wave transmission inside the higher‐density plasmasphere is more efficient. Data analysis indicates that the antenna impedance does not vary systematically with the antenna orientation angle relative to the ambient magnetic field. The previous dominant theoretical studies yield not only incorrect values of the impedance but a completely different frequency dependence than that derived from DSX experiments. Instead, the recent theories correctly capture both the antenna impedance magnitude and the frequency dependence. Plain Language Summary: Relativistic electrons in Earth's radiation belts pose severe threats to spacecraft and astronauts because of high‐level radiation from such energetic electrons. To mitigate the threat and damage to technology assets in space, artificial processes may be introduced to clear these particles or reduce their lifetime. Placing a whistler wave (in the frequency range about 3–30 kHz) transmitter in radiation belts may be the most direct approach to cause these high energy particles precipitating along the magnetic field lines into Earth's atmosphere and removed. On 25 June 2019, the Demonstration and Science Experiments (DSX) satellite of the US Air Force Research Laboratory was launched into medium‐Earth orbits. Onboard the DSX is a novel transmitter, called Transmitter‐Narrow‐band receiver‐Tuner. This paper describes in detail the data analysis methods and results. It is shown that space‐borne very low frequency transmission is possible with power transmitted up to 80 W for an 82‐m long tip‐to‐tip antenna. The study also indicated that the previous dominant theoretical studies yield not only incorrect values of antenna impedance but predicate completely different frequency dependence than that shown by the data from DSX experiments. Instead, the recent theories correctly capture both the antenna impedance magnitude and the frequency dependence. Key Points: The radiation resistance of the Demonstration and Science Experiments dipole antenna is up to several tens of thousand Ohms, and high‐power very low frequency transmission is feasible The antenna reactance roughly depends on the inverse of wave frequency, and resistance decreases with the inverse of frequency squared Antenna impedance derived confirms recent theoretical studies and disproves earlier influential theories